2021
DOI: 10.26508/lsa.202000905
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Glandirana rugosa using unsupervised AI reveals a high CG frequency

Abstract: The Japanese wrinkled frog (Glandirana rugosa) is unique in having both XX-XY and ZZ-ZW types of sex chromosomes within the species. The genome sequencing and comparative genomics with other frogs should be important to understand mechanisms of turnover of sex chromosomes within one species or during a short period. In this study, we analyzed the newly sequenced genome of G. rugosa using a batch-learning self-organizing map which is unsupervised artificial intelligence for oligonucleotide compositions. To clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…4E) (Abe et al, 2006c), 12 Drosophila species (Fig. 4F) , eight frogs (Katsura et al, 2021) and 13 plant species and found high separation ability even for closely related species.…”
Section: Analyses Of Various Eukaryotic Genomesmentioning
confidence: 88%
“…4E) (Abe et al, 2006c), 12 Drosophila species (Fig. 4F) , eight frogs (Katsura et al, 2021) and 13 plant species and found high separation ability even for closely related species.…”
Section: Analyses Of Various Eukaryotic Genomesmentioning
confidence: 88%
“…S8, we show examples of the three longest scaffolds of all three bats, and evident terminal peaks and internal peaks are observed, although their height and thickness vary among species. It should also be noted that we have previously observed Mb-level CpG islands near the ends of frog chromosomes [33], and the evolutionary processes that formed the Mb-level CpG islands are therefore of interest.…”
Section: Analyses Of Cg-containing Degepentas In Three Batsmentioning
confidence: 81%
“…S8, we show examples of the three longest scaffolds of all three bats, and evident terminal peaks and internal peaks are observed, although their height and thickness vary among species. It should also be noted that we have previously observed the Mb-level CpG islands near the ends of frog chromosomes [27], and therefore, the evolutionary processes that formed the Mb-level CpG islands are of interest.…”
Section: Analyses Of Cg-containing Degepenta In the 3 Batsmentioning
confidence: 86%